(untitled) (Jurnal Bahasa, 2020)
This paper discusses the spoken Malay dialect in the Pasir Raja subdistrict. From the perspective of folk linguistics, this dialect is deemed distinctive from the general Terengganu dialect. This thus raises a few issues that need to be addressed, namely (i) the phonological features that render the dialect different from other Malay dialects, and (ii) the relationship between this dialect and the other dialects in the eastern region of Peninsular Malaysia. To address these issues, the present study collected and recorded more than 600 words and conversations in the Pasir Raja dialect as its corpus. Based on the diachronic dialectology approach, this study describes some phonological features of the dialect and compares them with the features of Proto-Malayic and several other Malay dialects. This comparison was made for classification purposes. A number of phonological features discovered in the Pasir Raja dialect suggest the dialect is to be included as a branch of the Malay dialects of the interior on the eastern part of the Peninsula. Apart from the linguistic evidence, the close connection between the dialects is also proven by historical and sociological evidence. The significance of this study is the discovery of the existence of another Malay dialect in the east of the Peninsula. Keywords: Dialectology, Proto-Malayic, interior eastern dialects of the Malay Peninsula, innovation and retention, classification